A polyamide composite material and its preparation method and application

Through the combination technology of DOPO compound-coated glass fibers and iodine-containing compounds with organic phosphinate flame retardant, the existing problem of low GWIT of phosphinate flame retardant polyamides is solved, and high flame retardant and High impact strength polyamide composite material.

CN117363004BActive Publication Date: 2025-02-11KINGFA SCI & TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311514097.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2025-02-11
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

The existing phosphinate flame retardant polyamide has low flame retardant efficiency and low glow wire ignition temperature (GWIT), making it difficult to meet the performance requirements of plastic parts in household appliances.

Method used

The design of DOPO-like compounds coated with glass fibers and iodine-containing compounds and the mutual combination of organic phosphinate flame retardant and synergistic flame retardant is improved.

Benefits of technology

It significantly improves the GWIT of polyamide composite materials, enhances its flame retardant and mechanical properties, and performs excellently in impact strength, meeting the performance needs of electronics, electrical and energy storage industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004548457640000031
    Figure BDA0004548457640000031
  • Figure BDA0004548457640000061
    Figure BDA0004548457640000061
  • Figure BDA0004548457640000081
    Figure BDA0004548457640000081
Patent Text Reader

Abstract

The present invention provides a polyamide composite material and a preparation method and application thereof, wherein the polyamide composite material comprises the following components by mass: 20-60 parts of polyamide resin, 13-30 parts of organic phosphinate flame retardant, 4-10 parts of synergistic flame retardant, 15-40 parts of DOPO compound-coated glass fiber, and 0.2-2 parts of iodine-containing compound. The present invention significantly improves the GWIT of the polyamide composite material through the design and compounding of DOPO compound-coated glass fiber and iodine-containing compound, and cooperates with the organic phosphinate flame retardant and the synergistic flame retardant, and has good flame retardant and mechanical properties, especially high impact strength, which fully meets the performance requirements of industries such as electronic appliances, energy storage, and connectors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polyamide composite material and a preparation method and application thereof. Background Art

[0002] Polyamide (PA), commonly known as nylon, is an important thermoplastic engineering plastic. It is widely used in automobiles, mechanical parts, electronic appliances, home appliances, new energy and other fields due to its many excellent properties such as high strength, good self-lubrication, wear resistance, oil resistance and easy molding and processing. As a typical organic polymer material, polyamide has a low oxygen index and is ignited when it comes into contact with flames. When it burns, it produces a large amount of flame droplets and releases a lot of heat and gas. Therefore, when polyamide is used in products with fire safety requirements such as electronic appliances, automobiles, and new energy, it must be flame-retardant treated.

[0003] The flame retardants commonly used in polyamide can be roughly divided into halogen flame retardant systems and halogen-free flame retardant systems. The halogen flame retardant system has good flame retardant efficiency, but its high temperature stability is insufficient. Moreover, it will release harmful gases while flame retardant the polymer, which cannot meet the requirements of environmental protection. In recent years, it has been gradually replaced by the halogen-free flame retardant system. The halogen-free flame retardant system is mainly composed of nitrogen flame retardants and phosphorus flame retardants. Among them, phosphinate flame retardants have attracted much attention as a new type of environmentally friendly phosphorus flame retardant. Phosphinate flame retardant polyamide has excellent comprehensive mechanical properties, easy coloring, easy processing, high tracking index CTI, etc., and is commonly used in connectors, low-voltage electrical appliances, energy storage and other industries. However, the flame retardant efficiency of phosphinate flame retardant is low when used alone, and its flame retardant mechanism is mainly condensed phase and supplemented by gas phase. Therefore, the efficiency of capturing free radicals is much lower than that of bromine flame retardants, resulting in a low glow wire ignition temperature (GWIT) of phosphinate flame retardant polyamide, which is difficult to meet the performance requirements of plastic parts in household appliances.

[0004] In order to improve the flame retardancy and GWIT of phosphinate flame retardant polyamide, different flame retardants are usually used in combination with phosphinate flame retardants in the industry. For example, CN111315810A discloses a polyamide composition, comprising the following components: 30wt%-80wt% polyamide, 5wt%-50wt% inorganic fiber, 5wt%-40wt% flame retardant system, wherein the flame retardant system comprises zinc phosphinate and nitrogen-containing polyphosphate; the polyamide composition exhibits a glow-wire ignition temperature of 775°C or greater, although the glow-wire ignition temperature is improved compared to the polyamide material with only phosphinate flame retardant, the degree of improvement is low. CN109694568A discloses a high glow-wire halogen-free flame-retardant polyamide composite, which includes, by weight percentage: 40-90% polyamide resin, 2-25% organic phosphite flame retardant, 1-40% melamine flame retardant, 1-10% phosphate flame retardant, 0-45% reinforcing agent, and 0.1-3% other additives; the composite improves the glow-wire performance and flame retardant performance by adding phosphate flame retardant. CN112300570A discloses a silicon / phosphorus synergistic flame retardant polyamide resin, which is prepared by melt blending polyamide resin 50%-98%, 0.1%-10% silsesquioxane, 1%-30% organic phosphite, 0%-40% glass fiber, 0%-0.5% anti-dripping agent, and 0.1%-2% antioxidant under certain conditions, and provides excellent flame retardant effect through silicon / phosphorus synergy. Although the use of phosphate flame retardants and silsesquioxanes can improve the flame retardancy of phosphinate flame-retardant polyamides, the poor dispersibility of flame retardants in polyamide resin systems can easily lead to a decrease in mechanical properties, especially significantly deteriorating the impact strength of polyamide materials.

[0005] Therefore, developing a polyamide material with excellent flame retardancy and mechanical properties, high impact strength and high glow-wire ignition temperature is an urgent problem to be solved in the art. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a polyamide composite material and a preparation method and application thereof. By coating glass fiber with DOPO-type compounds and introducing iodine-containing compounds and compounding them with organic phosphite flame retardants and synergistic flame retardants, the glow-wire ignition temperature (GWIT) of the polyamide composite material is significantly improved, the flame retardancy is good, and it has high impact strength and excellent mechanical properties.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a polyamide composite material, wherein the polyamide composite material comprises the following components in parts by mass:

[0009]

[0010] The polyamide composite material provided by the present invention introduces DOPO compounds to coat glass fibers, wherein DOPO compounds are a type of phosphaphenanthrene flame retardants containing aromatic ring structures, have excellent carbon-forming flame retardant effects, and can strengthen condensed phase flame retardancy, but their single addition easily leads to reduced mechanical properties of the material. The present invention coats DOPO compounds on glass fibers, which can effectively weaken the candle wick effect of glass fibers, and cooperate with organic phosphinate flame retardants and synergistic flame retardants to improve the GWIT of polyamide composite materials. At the same time, the iodine-containing compound can efficiently capture the free radicals generated when the polymer decomposes, thereby improving GWIT. The present invention uses the design and compounding of DOPO-coated glass fibers and iodine-containing compounds, and cooperates with organic phosphinate flame retardants and synergistic flame retardants, so that the polyamide composite material has high GWIT and excellent flame retardancy, and also has excellent mechanical properties, especially excellent performance in terms of impact performance, which fully meets the performance requirements of industries such as electronics, energy storage, and connectors.

[0011] In the present invention, the term "DOPO" means 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide The term "DOPO-type compounds" includes DOPO and / or DOPO derivatives, wherein the DOPO derivatives include any one or a combination of at least two of compounds in which the H on the P atom in DOPO is replaced by other groups, compounds in which the benzene ring in DOPO is attached with substituents, and compounds in which the H on the P atom in DOPO is replaced by other groups and the benzene ring is attached with substituents.

[0012] In the polyamide composite material of the present invention, the mass parts of the polyamide resin are 20-60 parts, for example, it can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0013] The mass parts of the organic phosphinate flame retardant are 13-30 parts, for example, 14 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 27 parts or 29 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0014] The mass fraction of the synergistic flame retardant is 4-10 parts, for example, it can be 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0015] The mass percentage of the DOPO-type compound coated glass fiber is 15-40 parts, for example, it can be 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts or 38 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0016] The mass fraction of the iodine-containing compound is 0.2-2 parts, for example, it can be 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.1 parts, 1.3 parts, 1.5 parts, 1.7 parts or 1.9 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] In the present invention, by designing and compounding the components in specific amounts, the polyamide composite material has both high GWIT and high impact strength, and achieves an excellent balance effect in terms of mechanical properties, flame retardancy and high GWIT. If the mass fraction of the iodine-containing compound is too low, the GWIT of the polyamide composite material cannot be effectively improved; if the mass fraction of the iodine-containing compound is too high, the impact strength of the polyamide composite material will decrease.

[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0019] In the present invention, the polyamide resin includes any one of a condensation product of a dicarboxylic acid and a diamine, a condensation product of an ω-amino acid, and a ring-opening polymerization product of a cyclic lactam, or a combination of at least two thereof.

[0020] The dicarboxylic acid illustratively includes but is not limited to: any one of adipic acid, sebacic acid, dodecanedioic acid, terephthalic acid, and isophthalic acid, or a combination of at least two thereof.

[0021] The diamines illustratively include, but are not limited to, any one of hexamethylenediamine, decanediamine, dodecanediamine, butanediamine, p-phenylenediamine, and m-phenylenediamine, or a combination of at least two thereof.

[0022] The cyclic lactam illustratively includes, but is not limited to, any one of caprolactam, capryllactam, undecanolactam, and lauryl lactam, or a combination of at least two thereof.

[0023] The ω-amino acid illustratively includes, but is not limited to, any one or a combination of at least two of the ω-amino acids formed by the ring-opening of the aforementioned cyclic lactams and aminobenzoic acid.

[0024] Preferably, the polyamide resin includes any one of polyamide 66 (polyhexamethylene adipamide, PA66), polyamide 610 (PA610), polyamide 612 (PA612), polyamide 1010 (PA1010), polyamide 1012 (PA1012), polyamide 1212 (PA1212), polyamide 6 (polycaprolactam, PA6), polyamide 11 (PA11), and polyamide 12 (PA12), or a combination of at least two of them.

[0025] Preferably, the relative viscosity of a concentrated sulfuric acid solution of the polyamide resin at a concentration of 0.01 g / mL at 25° C. is 2.0-3.4, for example, it may be 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1 or 3.3, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0026] Exemplarily, the relative viscosity test method is as follows: weigh 0.5g of polyamide resin, transfer it to a 50mL volumetric flask, add about 40mL of concentrated sulfuric acid (the mass percentage of H2SO4 is 96%), and ultrasonically oscillate until the polyamide resin is completely dissolved, cool the solution to 25°C, dilute it to the scale with concentrated sulfuric acid, and mix it evenly. Test the flow time of 0.01g / mL of polyamide resin solution through the Ubbelohde viscometer at 25°C, recorded as t1, and use the same viscometer to test the flow time of the solvent concentrated sulfuric acid, recorded as t2, t1 / t2 is the relative viscosity of the polyamide resin.

[0027] Preferably, the organic phosphinate flame retardant has a structure as shown in Formula I:

[0028]

[0029] In Formula I, R1 and R2 are each independently selected from any one of a C1-C6 straight chain or branched alkyl group and a C3-C6 cycloalkyl group; wherein the C1-C6 straight chain or branched alkyl group may be a C1, C2, C3, C4, C5, or C6 straight chain or branched alkyl group, illustratively including but not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, etc.; the C3-C6 cycloalkyl group may be a C3, C4, C5, or C6 cycloalkyl group, such as cyclopropyl, cyclobutyl, cyclopentyl, or cyclohexyl.

[0030] In Formula I, M n+ It represents a +n-valent metal ion, where n is 2 or 3.

[0031] Preferably, R1 and R2 are each independently selected from any one of a C1-C4 straight chain or branched chain alkyl group and a cyclohexyl group.

[0032] Preferably, the M n+ Selected from Al 3+ or Zn 2+ .

[0033] Preferably, the organic phosphinate flame retardant includes any one of diethyl aluminum phosphinate, diethyl zinc phosphinate, methyl ethyl aluminum phosphinate, methyl butyl aluminum phosphinate, dipropyl aluminum phosphinate, and methyl cyclohexyl aluminum phosphinate, or a combination of at least two thereof.

[0034] Preferably, the organic phosphinate flame retardant comprises aluminum diethylphosphinate.

[0035] Preferably, the synergistic flame retardant includes any one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate, or a combination of at least two thereof, and melamine polyphosphate and / or zinc borate are further preferred.

[0036] Preferably, in the DOPO-type compound coated glass fiber, based on the mass of the glass fiber as 100%, the mass of the DOPO-type compound is 1%-5%, for example, it can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values ​​included in the said range, and 2%-4% is further preferred.

[0037] In the present invention, the coating amount = 100% × the mass of the DOPO compound / the mass of the glass fiber; that is, the coating amount of the DOPO compound in the DOPO compound coated glass fiber is preferably 1%-5%, and further preferably 2%-4%, thereby making the DOPO compound form a uniform and effective coating on the glass fiber, which can significantly inhibit the wick effect of the glass fiber on the one hand, and on the other hand, the DOPO compound coated glass fiber (especially the DOPO compound) and the organic phosphinate flame retardant and the synergistic flame retardant cooperate with each other, so that the polyamide composite material has high GWIT, excellent flame retardancy, high impact strength and excellent mechanical properties. If the coating amount of the DOPO compound is low, it cannot form an effective coating on the glass fiber, and the GWIT of the polyamide composite material is low; if the coating amount of the DOPO compound is too high, the impact strength of the polyamide composite material will decrease and the mechanical properties will decay.

[0038] Exemplarily, the coating amount of the DOPO-type compound coated glass fiber can be tested by the following method: respectively testing the mass m1 of the glass fiber before coating and the mass m2 of the DOPO-type compound coated glass fiber after coating, coating amount = 100% × (m2-m1) / m1.

[0039] Preferably, the DOPO compound has a structure as shown in Formula II:

[0040]

[0041] In formula II, R is selected from any one of hydrogen, substituted or unsubstituted C1-C10 straight or branched alkyl, and substituted or unsubstituted C6-C20 aryl.

[0042] The substituents in R are selected from hydroxyl, halogen, carboxyl, amino, nitro, C2-C6 ester or At least one of the groups, the dotted line represents the attachment site of the group.

[0043] Wherein, the C1-C10 straight chain or branched alkyl group can be a straight chain or branched alkyl group of C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, illustratively including but not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, 2-ethylhexyl, n-octyl, n-heptyl, n-nonyl, n-decyl, etc.

[0044] The C6-C20 aryl group may be an aryl group of C6, C9, C10, C12, C14, C16, C18, etc., and illustratively includes but is not limited to: phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, indenyl, fluorenyl and its derivative groups, fluoranthenyl, triphenylene, pyrenyl, peryl, Base, tetraphenyl, etc.

[0045] The halogen includes fluorine, chlorine, bromine or iodine.

[0046] The ester group can be understood as COOR 11 , where R 11 It may be a C1-C5 (eg, C1, C2, C3, C4, C5) straight chain or branched chain alkyl group.

[0047] Preferably, the DOPO compound includes 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, )、9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-hydroxymethyl-10-oxide (ODOPM, )、10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (DP-HQ, ), and further preferably includes DOPO.

[0048] Preferably, the glass fiber in the DOPO-based compound coated glass fiber includes any one of alkali-free glass fiber (E glass fiber), high alkali glass fiber (A glass fiber), special glass fiber (S glass fiber), D glass fiber, medium alkali glass fiber (C glass fiber), and quartz glass fiber, or a combination of at least two of them, and alkali-free glass fiber (E glass fiber) is further preferred.

[0049] Preferably, the diameter of the glass fiber is 1-30 μm, for example, it can be 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 5-15 μm is further preferred.

[0050] Preferably, the average length of the DOPO-type compound coated glass fiber is 100-800 μm, for example, it can be 200 μm, 300 μm, 400 μm, 500 μm, 600 μm or 700 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 200-600 μm is further preferred.

[0051] As a preferred technical solution of the present invention, the DOPO-type compound-coated glass fiber enters a melt blending device (such as a screw extruder, preferably a twin-screw extruder) in the form of continuous long fibers, and is sheared by the device to form short-cut DOPO-type compound-coated glass fibers with an average length of 100-800 μm, more preferably 200-600 μm, which exist in the polyamide composite material.

[0052] The present invention does not impose any particular limitation on the preparation method of DOPO compound-coated glass fiber. Any method known in the art for coating DOPO compound on the surface of glass fiber to obtain the DOPO compound-coated glass fiber is applicable to the present invention.

[0053] Exemplarily, the DOPO-type compound coated glass fiber is prepared by the following method, which includes: allowing the glass fiber to enter from the inlet of a coating device loaded with molten DOPO-type compound, and pulling it out from the outlet by a pulling device to obtain the DOPO-type compound coated glass fiber.

[0054] Preferably, the internal temperature of the coating device is 160-220°C, for example, it can be 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C or 215°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 170-200°C is further preferred; this temperature keeps the DOPO compound in the coating device in a molten state.

[0055] Preferably, the traction rate of the traction device is 5-50 cm / s, for example, it can be 8 cm / s, 10 cm / s, 15 cm / s, 20 cm / s, 25 cm / s, 30 cm / s, 35 cm / s, 40 cm / s or 45 cm / s, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; by controlling the traction rate, the DOPO compound coating amount can be controlled, and the DOPO compound coated glass fiber with different DOPO compound coating amounts can be prepared.

[0056] Preferably, the iodine-containing compound includes any one of metal iodide, non-metal iodide, iodate, or a combination of at least two of them.

[0057] Preferably, the iodine-containing compound includes any one of potassium iodide, calcium iodide, zinc iodide, nickel iodide, ammonium iodide, tetrabutylammonium iodide, potassium iodate, calcium iodate, and barium iodate, or a combination of at least two of them.

[0058] It should be noted that the aforementioned iodine-containing compound may be an anhydrous compound and / or a hydrate thereof; illustratively, the calcium iodide includes anhydrous calcium iodide and / or calcium iodide tetrahydrate.

[0059] It should be noted that the polyamide composite material of the present invention may also include any other additives that are added with motivation in the art.

[0060] Preferably, the polyamide composite material further comprises an antioxidant and / or a lubricant.

[0061] Preferably, the polyamide composite material further includes 0.01-0.8 parts of antioxidant by weight, and the antioxidant may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts or 0.7 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0062] Preferably, the antioxidant includes any one of hindered phenol antioxidants, amine antioxidants, phosphite antioxidants, cuprous halide composite antioxidants, and benzophenone antioxidants, or a combination of at least two thereof.

[0063] Preferably, the polyamide composite material further includes 0.01-1 parts of lubricant by mass, and the mass parts of the lubricant can be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or 0.9 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0064] Preferably, the lubricant includes any one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants, or a combination of at least two thereof, and ester lubricants are more preferred.

[0065] Preferably, the ester lubricant includes any one of fatty acid ester, polyol ester, polyethylene glycol ester, or a combination of at least two thereof.

[0066] In a preferred technical solution, the polyamide composite material comprises the following components in parts by mass:

[0067]

[0068] In the polyamide composite material provided by the present invention, polyamide resin is used as the main resin. Preferably, the mass percentage of the polyamide resin in the polyamide composite material is 35-60%, for example, it can be 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55% or 58%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0069] The DOPO-type compound coated glass fiber has a reinforcing effect. Preferably, the mass percentage of the DOPO-type compound coated glass fiber in the polyamide composite material is 15-35%, for example, it can be 18%, 20%, 22%, 25%, 28%, 30%, 32% or 34%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0070] In a second aspect, the present invention provides a method for preparing the polyamide composite material as described in the first aspect, the preparation method comprising:

[0071] The polyamide resin, the organic phosphinate flame retardant, the synergistic flame retardant and the iodine-containing compound are first mixed to obtain a premix;

[0072] The premix and the DOPO compound coated glass fiber are melt-blended and then extruded to obtain the polyamide composite material.

[0073] Preferably, the first mixed material further comprises an antioxidant and / or a lubricant;

[0074] Preferably, the first mixing is performed in a high-speed mixer.

[0075] Preferably, the first mixing time is 1-20 min, for example, 2 min, 5 min, 8 min, 10 min, 12 min, 15 min or 18 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 3-10 min is further preferred.

[0076] Preferably, the temperature of the first mixing is 15-40°C, for example, it can be 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C or 38°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and room temperature is further preferred.

[0077] Preferably, the melt blending is carried out in a screw extruder, and the screw extruder is preferably a twin-screw extruder.

[0078] Preferably, the temperature of each section of the screw barrel of the screw extruder is independently 150-280°C, for example, it can be 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 160-250°C is further preferred.

[0079] Preferably, the head temperature of the screw extruder is 220-280°C, for example, it can be 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C or 270°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 230-260°C is further preferred.

[0080] Preferably, the screw speed of the screw extruder is 200-1000rpm, for example, it can be 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or 900rpm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 300-800pm is further preferred.

[0081] Preferably, the screw extruder has a screw length-to-diameter ratio of (32-52):1, for example, 36:1, 40:1, 44:1 or 48:1, etc., and more preferably (36-48):1.

[0082] Preferably, the extrusion further includes the steps of drawing, cooling and pelletizing.

[0083] In a preferred technical solution, the method for preparing the polyamide composite material comprises:

[0084] A polyamide resin, an organic phosphite flame retardant, a synergistic flame retardant, an iodine-containing compound, an optional antioxidant and an optional lubricant are mixed for 3-10 minutes to obtain a premix; the premix is ​​added to the main feeding hopper of a twin-screw extruder, and the DOPO-type compound-coated glass fiber is added from the side feeding hopper of the sixth section of the screw barrel, and after sufficient plasticization and melt blending, it is extruded, and after drawing, cooling and pelletizing, the polyamide composite material is obtained; wherein the screw speed of the twin-screw extruder is 300-800rpm, the screw aspect ratio is (36-48):1, the temperature of each section of the screw barrel is independently 160℃-250℃, and the head temperature is 230℃-260℃.

[0085] In a third aspect, the present invention provides a use of the polyamide composite material as described in the first aspect in electronic appliances, energy storage devices or connectors.

[0086] Preferably, the polyamide composite material is used in connectors, miniature circuit breaker housings, and the like.

[0087] Compared with the prior art, the present invention has the following beneficial effects:

[0088] (1) In the polyamide composite material provided by the present invention, the GWIT of the polyamide composite material is significantly improved through the design and compounding of DOPO-type compound-coated glass fiber and iodine-containing compound, and the synergistic flame retardant and the organic phosphite flame retardant are used together to improve the flame retardant and mechanical properties of the polyamide composite material, especially the high impact strength, which fully meets the performance requirements of the electronic appliances, energy storage, connectors and other industries.

[0089] (2) The present invention designs, compounds and optimizes the components so that the GWIT of the polyamide composite material is ≥800°C and the notched impact strength is ≥110 J / m. The polyamide composite material has high GWIT, excellent flame retardant properties and mechanical properties, and is a flame retardant polyamide composite material with high impact strength and high GWIT. DETAILED DESCRIPTION

[0090] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0091] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0092] In the present invention, the features defined as "first" or "second" may include one or more of the features explicitly or implicitly, and are used to distinguish and describe the features, without distinction of order or importance. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0093] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0094] (1) Polyamide resin

[0095] PA66, specifically PA66 EPR24, with a relative viscosity of 2.4, purchased from Shenma Group;

[0096] PA6, specifically PA6 HY2800A, with a relative viscosity of 2.8, was purchased from Haiyang Chemical Fiber.

[0097] (2) Organic phosphinate flame retardants

[0098] Aluminum diethylphosphinate, Exolit OP 1230, was purchased from Clariant.

[0099] (3) Synergistic flame retardants

[0100] Melamine polyphosphate, Budit 3141, was purchased from Budit.

[0101] (4) DOPO-based compounds coated glass fibers

[0102] Specifically, it is DOPO coated glass fiber, wherein the glass fiber is alkali-free glass fiber (diameter is about 10 μm), and the length of the DOPO coated glass fiber is 200-500 μm. According to the different DOPO coating amounts, there are the following specific types:

[0103] DOPO coated glass fiber A, the coating amount of DOPO is 2%;

[0104] DOPO coated glass fiber B, the coating amount of DOPO is 1%;

[0105] DOPO coated glass fiber C, the coating amount of DOPO is 5%;

[0106] DOPO coated glass fiber D, the coating amount of DOPO is 0.5%;

[0107] DOPO coated glass fiber E, the coating amount of DOPO is 8%.

[0108] (5) Glass fiber

[0109] Alkali-free glass fiber, ERS200-13-T635B, roving, was purchased from Taishan Glass Fiber Co., Ltd.

[0110] (6) DOPO: purchased from Aladdin.

[0111] (7) Iodine-containing compounds

[0112] Potassium iodide, purchased from Aladdin;

[0113] Calcium iodate, purchased from Aladdin;

[0114] Tetrabutylammonium iodide, purchased from Aladdin;

[0115] Calcium iodide tetrahydrate, purchased from Aladdin;

[0116] Nickel iodide was purchased from Aladdin.

[0117] (8) Potassium bromide, purchased from Aladdin.

[0118] (9) Antioxidants

[0119] Hindered phenol antioxidant, IRGANOX 1098, was purchased from BASF.

[0120] (10) Lubricant

[0121] Ester lubricant, TR044W, was purchased from Struktol.

[0122] Example 1

[0123] A polyamide composite material and a preparation method thereof, wherein the polyamide composite material comprises the following components in parts by mass:

[0124]

[0125] The preparation method of the polyamide composite material is as follows:

[0126] (1) PA66 EPR24, aluminum diethylphosphinate, melamine polyphosphate, potassium iodide, antioxidant IRGANOX 1098 and lubricant TR044W were mixed in a high-speed mixer for 5 minutes according to the above formula to obtain a premix;

[0127] (2) The premix is ​​added into the main feeding hopper of a twin-screw extruder, and the DOPO-coated glass fiber A is added from the side feeding hopper of the sixth screw barrel. The screw speed of the twin-screw extruder is 400 rpm, the screw aspect ratio is 40:1, the temperatures of each section of the screw barrel are 160°C, 250°C, 240°C, 240°C, 220°C, 220°C, 220°C, 230°C, and 230°C, respectively, and the head temperature is 250°C, so that each component is fully plasticized, melt-blended and then extruded, and the polyamide composite material is obtained through drawing, cooling, and pelletizing.

[0128] Examples 2-13, Comparative Examples 1-5

[0129] A polyamide composite material, which differs from Example 1 only in the types and / or amounts of components, as shown in Tables 1 and 2, wherein "--" represents that the component is not added; the preparation method of the polyamide composite material is the same as that of Example 1.

[0130] Table 1

[0131]

[0132]

[0133] Table 2

[0134]

[0135] The performance test of the polyamide composite materials provided in Examples 1-13 and Comparative Examples 1-5 was carried out, and the specific method is as follows:

[0136] (1) Glow wire ignition temperature (GWIT): injection molded square plates of 60 mm × 60 mm × 1.0 mm were tested according to the method in standard IEC60695-2-13:2021;

[0137] (2) Notched impact strength: tested according to the method in standard ASTM D256:2010;

[0138] (3) Vertical combustion: Injection molded 125 mm × 13 mm × 0.4 mm burning specimens were tested for flame retardancy according to UL 94 standard;

[0139] The test data is shown in Table 3:

[0140] Table 3

[0141]

[0142]

[0143] According to the performance test data in Table 3, the present invention significantly improves the GWIT of the polyamide composite material, specifically 800-825°C, through the design and compounding of DOPO-coated glass fiber and iodine-containing compounds, and cooperates with diethyl aluminum phosphinate and synergistic flame retardants. At the same time, it has excellent impact properties, and the notched impact strength is 110-123 J / m. It is a high-performance flame-retardant polyamide composite material with high strength and high GWIT.

[0144] In the present invention, the coating amount of DOPO compound in the DOPO compound coated glass fiber is designed to be 1%-5%, and compounded with other components, so that the polyamide composite material has both high GWIT and high impact strength. The DOPO coating amount in the DOPO coated glass fiber of Example 12 is too low, and the GWIT is not improved. The DOPO coating amount in Example 13 is too high, and the GWIT is improved, but the impact strength decreases rapidly.

[0145] The present invention designs and compounds a specific content of DOPO-type compounds to coat glass fibers and iodine-containing compounds, and cooperates with organic phosphite flame retardants and synergistic flame retardants to make the polyamide composite material have high GWIT and high impact strength. In Comparative Example 1, no iodine-containing compound is used, and its GWIT is only 750°C, but the impact strength is relatively high. In Comparative Example 2, DOPO is not coated on the glass fiber, but is directly added, resulting in a significant deterioration in the impact strength of the polyamide composite material. The reason may be that the dispersibility of DOPO in the polyamide system is poor; however, due to the effect of potassium iodide, its GWIT is improved compared with Comparative Example 1. In Comparative Example 3, the amount of potassium iodide added is too little, so the GWIT of the polyamide composite material is low; and in Comparative Example 4, the amount of potassium iodide added is too much, so the impact strength of the polyamide composite material is significantly reduced. In Comparative Example 5, potassium bromide is used instead of iodide, so the GWIT of the polyamide composite material is not improved.

[0146] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the polyamide composite material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polyamide composite material, characterized in that: The polyamide composite material comprises the following components in parts by mass: The synergistic flame retardant includes melamine polyphosphate; The iodine-containing compound includes any one of potassium iodide, calcium iodide, nickel iodide, tetrabutylammonium iodide, and calcium iodate, or a combination of at least two thereof; In the DOPO-based compound-coated glass fiber, the mass of the DOPO-based compound is 1%-5% based on the mass of the glass fiber being 100%; The DOPO compound has a structure as shown in Formula II: Wherein, R is selected from any one of hydrogen, substituted or unsubstituted C1-C10 straight or branched alkyl, substituted or unsubstituted C6-C20 aryl; The substituents in R are selected from hydroxyl, halogen, carboxyl, amino, nitro, C2-C6 ester or At least one of the groups, the dotted line represents the attachment site of the group.

2. The polyamide composite material according to claim 1, characterized in that: The polyamide resin includes any one of polyamide 66, polyamide 610, polyamide 612, polyamide 1010, polyamide 1012, polyamide 1212, polyamide 6, polyamide 11, and polyamide 12, or a combination of at least two of them.

3. The polyamide composite material according to claim 1, characterized in that: The organic phosphinate flame retardant has a structure as shown in Formula I: Wherein, R1 and R2 are each independently selected from any one of C1-C6 straight chain or branched chain alkyl and C3-C6 cycloalkyl; M n+ It represents a +n-valent metal ion, where n is 2 or 3.

4. The polyamide composite material according to claim 3, characterized in that: The R1 and R2 are each independently selected from any one of a C1-C4 straight chain or branched chain alkyl group and a cyclohexyl group.

5. The polyamide composite material according to claim 3, characterized in that: The M n+ Selected from Al 3+ or Zn 2+ .

6. The polyamide composite material according to claim 1, characterized in that: The organic phosphinate flame retardant includes aluminum diethylphosphinate.

7. The polyamide composite material according to claim 1, characterized in that: In the DOPO-based compound-coated glass fiber, based on the mass of the glass fiber being 100%, the mass of the DOPO-based compound is 2%-4%.

8. The polyamide composite material according to claim 1, characterized in that: The glass fiber in the DOPO-based compound coated glass fiber includes any one of alkali-free glass fiber, high-alkali glass fiber, special glass fiber, D glass fiber, medium-alkali glass fiber, and quartz glass fiber, or a combination of at least two thereof.

9. The polyamide composite material according to claim 8, characterized in that: The glass fiber in the DOPO-based compound coated glass fiber includes alkali-free glass fiber.

10. The polyamide composite material according to claim 1, characterized in that: The diameter of the glass fiber is 1-30 μm.

11. The polyamide composite material according to claim 10, characterized in that: The diameter of the glass fiber is 5-15 μm.

12. The polyamide composite material according to claim 1, characterized in that: The length of the DOPO compound coated glass fiber is 100-800 μm.

13. The polyamide composite material according to claim 12, characterized in that: The length of the DOPO compound coated glass fiber is 200-600 μm.

14. The polyamide composite material according to claim 1, characterized in that: The polyamide composite material further comprises an antioxidant and / or a lubricant.

15. The polyamide composite material according to claim 14, characterized in that: The polyamide composite material further comprises 0.01-0.8 parts by weight of an antioxidant.

16. The polyamide composite material according to claim 14, characterized in that: The antioxidant includes any one of hindered phenol antioxidants, amine antioxidants, phosphite antioxidants, cuprous halide composite antioxidants, and benzophenone antioxidants, or a combination of at least two of them.

17. The polyamide composite material according to claim 14, characterized in that: The polyamide composite material further comprises 0.01-1 parts by weight of lubricant.

18. The polyamide composite material according to claim 14, characterized in that: The lubricant includes any one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants, or a combination of at least two of them.

19. A method for preparing a polyamide composite material as claimed in claim 1, characterized in that: The preparation method comprises: The polyamide resin, the organic phosphinate flame retardant, the synergistic flame retardant and the iodine-containing compound are first mixed to obtain a premix; The premix and the DOPO compound coated glass fiber are melt-blended and then extruded to obtain the polyamide composite material.

20. The preparation method according to claim 19, characterized in that: The first mixed material further comprises an antioxidant and / or a lubricant.

21. The preparation method according to claim 19, characterized in that: The first mixing time is 1-20 min.

22. The preparation method according to claim 21, characterized in that: The first mixing time is 3-10 min.

23. The preparation method according to claim 19, characterized in that: The melt blending is carried out in a screw extruder.

24. The preparation method according to claim 23, characterized in that: The temperature of each section of the screw barrel of the screw extruder is independently 150-280°C.

25. The preparation method according to claim 24, characterized in that: The temperature of each section of the screw barrel of the screw extruder is independently 160-250°C.

26. The preparation method according to claim 23, characterized in that: The head temperature of the screw extruder is 220-280°C.

27. The preparation method according to claim 26, characterized in that: The head temperature of the screw extruder is 230-260°C.

28. The preparation method according to claim 19, characterized in that: The method further comprises the steps of drawing, cooling and pelletizing after the extrusion.

29. Use of the polyamide composite material according to any one of claims 1 to 18 in electronic appliances, energy storage devices or connectors.

Citation Information

Patent Citations

  • Flame retardant polyamide composition

    CN111315810A

  • Silicon / phosphorus synergistic flame-retardant polyamide resin

    CN112300570A

  • High-glow-wire halogen-free flame-retardant polyamide compound as well as preparation method and application thereof

    CN109694568A

  • Flame-retardant impact-resistant high-stability nylon composite material and preparation method thereof

    CN109852042A